2000
DOI: 10.1177/108705710000500305
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Screening Assay to Measure Epidermal Growth Factor Internalization

Abstract: Recently, we showed that the internalization of the epidermal growth factor (EGF) receptor is inhibited by hydrogen peroxide (H(2)O(2)) in human fibroblasts. In order to test the effect of various stress conditions on receptor internalization and to test a variety of antioxidants in their capacity to prevent or reduce the H(2)O(2)-induced inhibition of internalization, a screening assay was developed to measure the internalization in 96-well plates. In this assay, cells are exposed to biotin-conjugated EGF and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…EGFR internalization rates were determined by using the method of de Wit et al (33,34) with slight modification. Briefly, cells were plated at 20,000/well in 96-well plates, grown for 24 h, and then shifted to 1 g/ml tetracycline and 50 g/ml PEI-containing media for 24 h. To measure surface EGFR, cultures were washed and treated with 50 ng/ml biotin-labeled EGF (Invitrogen Molecular Probes) in PBS containing Ca 2ϩ /Mg 2ϩ /glucose for 1 h at 4°C, then washed with PBS and fixed in PBS containing 3% paraformaldehyde, 0.25% glutaraldehyde, and 0.25% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…EGFR internalization rates were determined by using the method of de Wit et al (33,34) with slight modification. Briefly, cells were plated at 20,000/well in 96-well plates, grown for 24 h, and then shifted to 1 g/ml tetracycline and 50 g/ml PEI-containing media for 24 h. To measure surface EGFR, cultures were washed and treated with 50 ng/ml biotin-labeled EGF (Invitrogen Molecular Probes) in PBS containing Ca 2ϩ /Mg 2ϩ /glucose for 1 h at 4°C, then washed with PBS and fixed in PBS containing 3% paraformaldehyde, 0.25% glutaraldehyde, and 0.25% Triton X-100.…”
Section: Methodsmentioning
confidence: 99%
“…Next, biotinylated EGF was used to quantify EGFR localization after EGF treatment (33,34). To measure surface EGFR, biotinylated EGF was incubated with WT, Y998A and 4A EGFR cells at 4°C for 1 h. HRP-conjugated streptavidin was used to quantify biotinylated EGF.…”
Section: And Smentioning
confidence: 99%
“…at 0°C. After being washed twice with cold PBS, total amounts of protein after different treatments were determined with protein assay reagent BCA as described by the manufacturer (Pierce, Rockford, Ill.), while the amount of internalized EGFbiotin in cells in other wells was determined as described previously (20).…”
Section: Egf-biotin Internalization Assay In 96-well Platesmentioning
confidence: 99%
“…Recently, we have found that H 2 O 2 inhibits the internalization of the EGF receptor in fibroblasts in a concentration-dependent manner (19,20). The internalization and subsequent degradation of activated EGF receptors is one of the negative-feedback mechanisms to attenuate EGF-induced signaling.…”
mentioning
confidence: 99%
“…The procedure has been described previously and was adopted for biotin-EGF-based microtitre assays. [50][51][52] Briefly, cells were serum starved for 12-16 h and pulsed with 100 ng/ml biotin-EGF for 0-10 min at 37°C in serum-free medium in the presence or absence of 100-fold molar excess unlabeled EGF. EGFR internalization was assessed by tracking surface and internalized levels of biotin-EGF over time using immunocytochemistry.…”
Section: Egfr Internalizationmentioning
confidence: 99%